Strategic alternatives for Muslim-friendly homestay in Sabah Malaysia: a SWOT/TOWS analysis - Suddin Lada; Brahim Chekima; Rudy Ansar; Lim, Ming Fook; Mohamed Bouteraa; Azaze Azizi Abdul Adis; Mohd Rahimie Abd Karim; Kelvin Yong (Emerald Group Publishing Limited, 2024)
Purpose This study aims to explore the strengths, weaknesses, opportunities and threats (SWOT) of the Muslim-friendly homestay business in Malaysia to help identify and recommend practical strategies to capitalize on the strengths and potentials while overcoming the current shortcomings and threats. Design/methodology/approach The Muslim-friendly business owner and operators in Sabah, Malaysia, were the subject of a series of focus groups and expert opinion interviews. The data was transcribed, and then the variables were categorized into the four SWOT categories using content and thematic analysis. Meanwhile, threats, opportunities, weaknesses and strengths (TOWS) analysis is used to identify the best strategy alternatives. Findings The SWOT analysis identifies several strengths (e.g. diverse and unique Islamic culture and heritage [S1], iconic Islamic landmarks [S2], rich natural beauty [S3], well-established halal tourism industry [S4]); weaknesses (e.g. limited awareness [W1], limited infrastructure and facilities [W2], limited human resources and trained personnel [W3], lack of Islamic tourism products and experiences [W4]); opportunities (e.g. growing demand for Islamic tourism [O1], increasing disposable income [O2], potential for collaborations [O3], potential for partnerships [O4], potential for expanding Sabah’s halal tourism offerings [O5]); and threats (e.g. competition [T1], political instability [T2], economic downturns [T3] and environmental and social challenges [T4]). Practical implications This paper could serve as a guideline and supplementary information for stakeholders in the homestay industry to grasp their business environment better. Originality/value To the best of the authors’ knowledge, this is the first study of its type to blend SWOT and TOWS analysis with the sector of Muslim-friendly homestays. Hence, the findings might expand understanding of the Muslim-friendly homestays industry and aid businesses in penetrating this growing market.